Computer-assisted Diagnosis of Dyspepsia — Report on Transferability of a System, with Emphasis on Early Diagnosis of Gastric Cancer - Zoltie, N.; Horrocks, J. C.; de Dombal, F. T. (Methods of Information in Medicine, 1977)
This paper reports a retrospective study of computer-assisted diagnosis of 86 cases of >dyspepsia< in Bristol, England; the computer-assisted diagnosis making use of a database provided by 360 patients from Leeds, England. The computer’s diagnostic prediction proved to be correct in 63 out of the 86 cases — an overall accuracy of 73.3%. The system correctly diagnosed 14 out of 18 cases of gastric cancer (77.8%) at the expense of only three false positives.These results (1) confirm that gastric cancer can be diagnosed in most cases on the history alone; (2) suggest that this method of assisting diagnosis can be transferred successfully to different localities without loss of accuracy; and (3) indicate that a detailed structured computer-assisted analysis of the patient’s symptoms may be of value in selecting high-risk patients for intensive investigation.
Keywords: Computer-assisted Diagnosis; Database; Cancer; Dyspepsia